AR-MO Model: Augmented Reality–Based Learning to Enhance Students’ Understanding and Skills in Molecular Geometry - Hani Dewi Ariessanti; Paramadinah Aqil Raditya; Nizirwan Anwar (MASI Mandiri Edukasi, 2026)
This study addresses the persistent difficulty Indonesian secondary students face in grasping abstract molecular geometry concepts, exacerbated by the limited adoption of immersive technologies in local curricula. We developed the AR-MO (Augmented Reality-Based Molecular) instructional model using a six-stage Design Science Research (DSR) approach, spanning from problem identification to the communication of results. The model’s effectiveness was evaluated among 349 students across 15 public high schools in Tangerang using a pre-test/post-test design, with data analyzed through descriptive statistics and category-shift mapping. Results indicate a significant enhancement in cognitive understanding, attitudes, and practical skills, with nine schools completely eliminating